2007
DOI: 10.1111/j.1365-2893.2007.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between lamivudine sensitivity and the number of substitutions in the reverse transcriptase region of the hepatitis B virus polymerase

Abstract: This study aimed to identify the viral factors responsible for poor sensitivity to lamivudine (LAM). We analyzed 49 LAM-treated chronic hepatitis B patients infected with hepatitis B virus (HBV) genotype C. Serum HBV DNA reached a level below the detection limit of the sensitive PCR assay in 31 (63.3%) within the first 24 weeks of LAM therapy (good responder group). Of the patients who did not achieve undetectable levels of HBV DNA within 24 weeks (poor responder group), 15 (83.3%) experienced virological brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…We have previously studied the association between lamivudine sensitivity and amino acid substitutions in the reverse transcriptase (RT) region of HBV polymerase and found that sequence analysis of the RT domain is useful for predicting sensitivity to LAM therapy [29].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously studied the association between lamivudine sensitivity and amino acid substitutions in the reverse transcriptase (RT) region of HBV polymerase and found that sequence analysis of the RT domain is useful for predicting sensitivity to LAM therapy [29].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, HBeAg-negative variants had a higher number of rt amino acid substitutions compared to the HBeAg-positive group. It is reasoned that higher number of rt amino acid changes in the active domain may affect the enzyme activity reducing the replication efficacy of the virus and contribute to treatment response [44] . Follow-up of these individuals is essential to identify if a greater number of rt amino acid substitutions in HBeAg-negative patients can reduce the risk of treatment failure.…”
Section: (G)mentioning
confidence: 99%
“…It is well known that drug resistance is associated with HBV DNA titer at week 24 after the initiation of lamivudine treatment [45][46][47]. Yuen et al studied the positive relationship between lamivudine resistance and HBV DNA level for 159 Chinese HBeAg positive patients.…”
Section: On Treatment Monitoringmentioning
confidence: 99%
“…The patient with complete virologic response has a very low risk of resistance [45][46][47]. In that case, the clinician should treat with the same regimen and monitor the response every 3∼6 months [48,49].…”
Section: ∼10mentioning
confidence: 99%
See 1 more Smart Citation